A Biorefinery Strategy That Introduces Hydrothermal Treatment Prior to Acid Hydrolysis for Co-generation of Furfural and Cellulose Nanocrystals - Beyene, Dawit; Chae, Michael; Vasanthan, Thava; Bressler, David C. (Frontiers in Chemistry, 2020)
Hydrothermal treatment of wood pulp at 150–225 °C prior to acid hydrolysis was investigated in the context of isolating cellulose nanocrystals (CNCs). The objective was two folds as follows: a) generating furfural as a value–added co–product; and b) concentrating and forming new CNC precursors through thermal re–orientation of para–crystalline cellulose chains that will in turn improve CNC recovery and yield. Furfural yields up to 19% and 21% xylan conversion were obtained at 200 and 225 °C hydrothermal treatments, respectively. In addition, these hydrothermal treatment conditions increased the crystallinity index of the pulp (77%) to 84% and 80%, respectively. Consequently, the CNC yield from hydrothermally treated wood pulp, when compared to untreated wood pulp, improved by up to 4 and 2 folds, respectively. An efficient acid hydrolysis process with yield improvements can translate to reduced CNC isolation and purification costs and increased production capacity. The qualities of the CNCs in terms of particle size and crystallinity were not affected due to hydrothermal treatment. However, the zeta potential, sulfur, hydrogen and oxygen content of the CNCs were significantly lower at 225 °C while carbon composition increased, and dark brown coloration was observed that indicates caramelization. This study demonstrates for the first time a novel biorefinery strategy that integrates hydrothermal treatment with acid hydrolysis to co–generate furfural and CNC with improved efficiency.